2000
DOI: 10.1016/s0925-4773(00)00359-2
|View full text |Cite
|
Sign up to set email alerts
|

The insect immune protein hemolin is expressed during oogenesis and embryogenesis

Abstract: Hemolin is the most abundant bacteria-induced proteins in Hyalophora cecropia hemolymph. Its structural features, both at the protein and gene level, ascribe this molecule to the immunoglobulin gene superfamily (IgSF) with particular homology to neural cell adhesion molecules. An increasing number of evidence suggest a role in immune recognition and in cell adhesion events. Hemolin is also developmentally regulated as suggested by changes in its concentration during larval and pupal ecdysis (Trenczek, T., 1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 3 publications
1
25
1
Order By: Relevance
“…5; Table 2), and these observations were not in agreement with previous reports that hemolin was abundantly expressed in larva (Lanz-Mendoza et al, 1996). Therefore, it is reasonable to suggest that hemolin plays a broader role from pupa to adult, perhaps also being involved in the normal development of oocytes and embryos, as that has been investigated previously in other insects (Bettencourt et al, 2000(Bettencourt et al, , 2002. Stan encodes the protocadherin-like wing polarity protein and participates in the fz (frizzled) signaling pathway responsible for controlling wing tissue polarity (Usui et al, 1999), which also initiates prehair morphogenesis and regulates tissue polarity and formation of normal dendrite fields (Chae et al, 1999).…”
Section: Identification Of Genes Related With Silkworm Metamorphosiscontrasting
confidence: 58%
“…5; Table 2), and these observations were not in agreement with previous reports that hemolin was abundantly expressed in larva (Lanz-Mendoza et al, 1996). Therefore, it is reasonable to suggest that hemolin plays a broader role from pupa to adult, perhaps also being involved in the normal development of oocytes and embryos, as that has been investigated previously in other insects (Bettencourt et al, 2000(Bettencourt et al, , 2002. Stan encodes the protocadherin-like wing polarity protein and participates in the fz (frizzled) signaling pathway responsible for controlling wing tissue polarity (Usui et al, 1999), which also initiates prehair morphogenesis and regulates tissue polarity and formation of normal dendrite fields (Chae et al, 1999).…”
Section: Identification Of Genes Related With Silkworm Metamorphosiscontrasting
confidence: 58%
“…Due to its adhesion properties, some hemolins have been involved in the cell adhesion mechanism (37). Some studies reveal that hemolins are present in neural tissues in several phases of embryonic development (24), and their expression correlates with hormones that regulate moulting and metamorphosis of lepidopters (19,45). It seems clear that hemolins are multifunctional proteins with roles in defense (cellular and humoral) and in development (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hemolin is a bacteria-inducible immunoglobulinlike protein whose role in insect immunity has been better studied. In the last 2 decades, independent studies have demonstrated that hemolin proteins are multifunctional molecules involved in a diverse range of cell interaction and are able to (a) bind lipopolysaccharides and be up-regulated in hemolymph during infections (15)(16)(17); (b) be up-regulated during metamorphosis (18,19); (c) promote opsonin-like effects, such as increased cell adhesion and phagocytosis (20,21); (d) agglutinate bacterial cells (17,22); (e) bind to hemocytes and inhibit their aggregation (15,20,22,23); and (f) regulate embryonic development (24,25).…”
mentioning
confidence: 99%
“…A hemolinlike cDNA was also cloned from the fall webworm, Hyphantria cunea [9]. Hemolin is synthesized mainly in fat body in response to microbial challenge [4,8], but it is also synthesized in the absence of infection in embryos [10] and in fat body and midgut during metamorphosis [3,11,12]. Hemolin expressed at different developmental stages of M. sexta differs in carbohydrate content.…”
mentioning
confidence: 99%